1982
DOI: 10.1111/j.1471-4159.1982.tb08710.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anticonvulsants on the Formation of γ‐Hydroxybutyrate from γ‐Aminobutyrate in Rat Brain

Abstract: The conversion of gamma-aminobutyrate (GABA) via succinic semialdehyde to gamma-hydroxybutyrate has been examined in rat brain homogenates. A number of anticonvulsants, including sodium valproate and phenobarbitone, inhibited this metabolic pathway. These results are interpreted in the light of the characteristics of aldehyde reductases known to reduce succinic semialdehyde.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 22 publications
(18 reference statements)
1
6
0
Order By: Relevance
“…Production of I4CO2 was markedly curtailed in the presence of malonic acid, and isotope accumulated in succinic acid. Valproic acid has been reported to inhibit GABA-aminotransferase and SSADH in ox brain (16) and rat brain (17)(18)(19)(20). We observed an inhibition of I4CO2 production from [U-14C]SSA in intact lymphoblasts in the presence of 5 mM valproic acid.…”
Section: I4c-ssa Oxidation In Human Lymphoblastssupporting
confidence: 52%
“…Production of I4CO2 was markedly curtailed in the presence of malonic acid, and isotope accumulated in succinic acid. Valproic acid has been reported to inhibit GABA-aminotransferase and SSADH in ox brain (16) and rat brain (17)(18)(19)(20). We observed an inhibition of I4CO2 production from [U-14C]SSA in intact lymphoblasts in the presence of 5 mM valproic acid.…”
Section: I4c-ssa Oxidation In Human Lymphoblastssupporting
confidence: 52%
“…In contrast to the potent effect of valproate on nonspecific SSAR, specific SSAR is not affected by the drug [104]. However, Whittle and Turner [105], using rat brain homogenates, demonstrated that valproate inhibited the formation ofGHB in vitro, which would indicate that the specific SSAR is not exclusively responsible for GHB formation but that the nonspecific (valproate sensitive) aldehyde reductase may also contribute to a significant extent to this metabolic pathway. Inhibition of GHB formation by valproate could be of considerable interest since this amino acid has been shown to produce epileptogenic effects in several species [106].…”
Section: Neurochemical Effects Of Valproate On the Gaba Systemmentioning
confidence: 89%
“…This is of interest in view of the fact that valproic acid has been reported to be an inhibitor of enzymes involved in GHB metabolism in ox brain (25) and rat brain (26)(27)(28)(29), succinic semialdehyde dehydrogenase and GABAtransaminase. The data when butyric acid was the substrate indicated clearly that~xidation was functional in the mitochondrial preparations under study.…”
Section: Discussionmentioning
confidence: 99%